Absenteísmo-doença em trabalhadores de enfermagem de um hospital universitário: estudo de métodos mistos - Prestes, Francine Cassol (2017)
The aim of this paper was to analyse sickness absenteeism and its association with the socio-occupational characteristics of nursing workers and its interfaces with the work context of a university hospital. This is a mixed method study with an explanatory sequential design. The investigation was carried out from November 2016 to June 2017. In the first stage (quantitative), a cross-sectional research design was used with document data sources. These documents included any records of sickness absences of nurses, nursing technicians, and nursing assistants working at the hospital and confirmed by a physician or dentist at the start of 2016. Other forms of absenteeism and sick leave records without an assigned sickness code were discarded. The second stage (qualitative) was based on a qualitative design and consisted of 20 interviews. The selection criteria were workers with at least one sick leave on record in the first stage; sick leave of no less than 14 days for reasons of mental or musculoskeletal illness; and subjects who were working during the interview period. In the first step, a form was used to characterise sickness absenteeism. The quantitative data were subjected to descriptive statistical analysis, considering p< 0.05 as the threshold of statistical significance. The qualitative data were collected through semi-structured interviews and subjected to thematic analysis. The methods were combined by connecting research stages and integrating results and discussion. The study was submitted for ethics approval and granted the certificate of ethical appreciation number 58956116.5.0000.5346. The records contained 1744 episodes of sickness absenteeism and 18,536 days of sick leave of nursing workers in the studied year. The most common causes of sick leave were mental illness (16.0%; n=278), respiratory tract diseases (15.2%; n=265), and musculoskeletal diseases (12.5%; n = 217). In relation to the number of days of absence from work, mental illnesses accounted for 6692 days (36.1%), followed by musculoskeletal diseases with 2286 days (12.3%). Mental diseases were associated with the statutory nature of employment (p=0.001), women (p=0.009), nursing assistant (p<0.001), duration ≥ 14 days (p<0.001), ≥ 41 years of age (p<0.001), and ≥ 9 years of employment (p<0.001). An association was found between musculoskeletal diseases and sick leaves of 3 to 13 days (p=0.010), men (p<0.001), position as nursing technician (p<0.001), between 9 and 13 years of employment (p=0.002), night shift (p=0.026), and three sick leaves in a year (p=0.010). Moreover, a interfaces was identified between sickness absenteeism and the context of nursing work, and sick leaves were related to the (dis) organisation of work, inadequate working conditions, and commitment of socio-occupational relations. The results showed sickness absenteeism is associated with the socio-occupational characteristics of nursing workers and it interfaces with the work context.